2018
DOI: 10.2478/eteals-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies, Multiple Literacies and Teaching English as a Foreign Language

Abstract: This article presents and briefly discusses the results from a survey conducted with English teachers of the third cycle and secondary education in Portugal as part of a study on multiple literacies and Web 2.0 in English as a foreign language (EFL) classroom (Cardoso). Based on the answers provided, it can be assumed that among this group of teachers, new technologies tend to be part of their professional practice. However, it is unclear if digital tools have been used to actually promote more innovative ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Learning management systems (LMSs) as a digital tool are thought to be an integral part of the recent digital turn in EFL teaching and learning (Kite et al, 2020;Lawrence et al, 2020). In light of the digital turn in EFL (Bensalem, 2019;Cardoso, 2018), LMSs "have become a key component of teaching and learning in higher education" (Kite et al, 2020: 183). The use of LMSs has a profound impact upon current practices of EFL Taking into consideration the current focus on LMSs in EFL research (Siahaan, 2020;Zhonggen et al, 2019), this article presents an empirical investigation that seeks to explore how pre-service EFL teachers (hereinafter "participants") frame their perceptions of LMS Canvas in their EFL studies.…”
Section: Introductionmentioning
confidence: 99%
“…Learning management systems (LMSs) as a digital tool are thought to be an integral part of the recent digital turn in EFL teaching and learning (Kite et al, 2020;Lawrence et al, 2020). In light of the digital turn in EFL (Bensalem, 2019;Cardoso, 2018), LMSs "have become a key component of teaching and learning in higher education" (Kite et al, 2020: 183). The use of LMSs has a profound impact upon current practices of EFL Taking into consideration the current focus on LMSs in EFL research (Siahaan, 2020;Zhonggen et al, 2019), this article presents an empirical investigation that seeks to explore how pre-service EFL teachers (hereinafter "participants") frame their perceptions of LMS Canvas in their EFL studies.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of recent studies that seek to discover how digital artifacts are used in EFL/ESL instructional contexts (Aloraini, 2018;Cardoso, 2018;García-Pastor, 2020;Irwin, 2019;Kessler, 2013;Kusumaningputri & Widodo, 2018;Kustini et al, 2020;Norton, 2019;Shuang & Zhang, 2020;Thoms et al, 2018). These studies are characterised by several research foci that elucidate the issue of digital artifacts from the vantage points of i) EFL/ESL teachers (Cardoso, 2018;Thoms et al, 2018), ii) EFL/ESL students (Aloraini, 2018;García-Pastor, 2020;Irwin, 2019;Kusumaningputri & Widodo, 2018;Norton, 2019;Shuang & Zhang, 2020), and iii) EFL/ESL researchers (Kessler, 2013;Kustini et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research focus on digital artifacts from the vantage point of EFL/ESL teachers is central in the studies conducted by Cardoso (2018), and Thoms et al (2018), who develop this focus in relation to a) the use of digital artifacts as an open-access teaching resource by ESL instructors in the USA (Thoms et al, 2018) and b) the assessment of the role of digital artifacts and digital technology by EFL secondary school teachers in Portugal (Cardoso, 2018). By means of conducting a survey, Thoms et al (2018) have found that the majority of American ESL teachers make use of such digital artifacts as YouTube videos in order to provide culturally appropriate instructional content.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations